2016
DOI: 10.1038/nrneurol.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Angelman syndrome — insights into a rare neurogenetic disorder

Abstract: Angelman syndrome is a rare neurogenetic disorder that is characterized by microcephaly, severe intellectual deficit, speech impairment, epilepsy, EEG abnormalities, ataxic movements, tongue protrusion, paroxysms of laughter, abnormal sleep patterns, and hyperactivity. Angelman syndrome results from loss of function of the imprinted UBE3A (ubiquitin-protein ligase E3A) gene on chromosome 15q11.2-q13. This loss of function can be caused by a mutation on the maternal allele, a 5-7 Mb deletion of the maternally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
267
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(282 citation statements)
references
References 109 publications
4
267
0
11
Order By: Relevance
“…However, as the healthy father had the identical genetic and biochemical phenotype and further studies in the index patient showed signs unusual for DPD deficiency, additional studies were performed that finally demonstrated AS. Characteristic signs of AS such as microcephaly, delayed development and characteristic EEG features were encountered in the patient (Buiting et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as the healthy father had the identical genetic and biochemical phenotype and further studies in the index patient showed signs unusual for DPD deficiency, additional studies were performed that finally demonstrated AS. Characteristic signs of AS such as microcephaly, delayed development and characteristic EEG features were encountered in the patient (Buiting et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A deletion of the maternal allele of chromosome 15q11.2-13-1 causative for AS was identified (Fig. 3) (Buiting et al 2016).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin and other adipokines are ideal candidates for such signalling molecules. Microcephaly, a number of neurological disorders, including intellectual and speech deficiencies, behavioural and sleep abnormalities and epilepsy Buiting et al, 2016 Prader-Willi syndrome (PWS, OMIM 176270)…”
Section: Energy Homeostasis and Resource Allocation During Pregnancymentioning
confidence: 99%